Control of bleeding in surgical procedures: critical appraisal of HEMOPATCH (Sealing Hemostat) - Lewis KM (Dove Medical Press, 2015)
Kevin Michael Lewis,1 Carl Erik Kuntze,2 Heinz Gulle3 1Preclinical Safety and Efficacy, Baxter Healthcare Corporation, Deerfield, IL, USA; 2Medical Affairs, Baxter Healthcare SA, Zurich, Switzerland; 3Surgical Sciences and Engineering, Baxter Medical Products GmbH, Vienna, Austria Abstract: The need for advanced hemostatic agents increases with the complexity of surgical procedures and use of anticoagulation and antiplatelet treatments. HEMOPATCH (Sealing Hemostat) is a novel, advanced hemostatic pad that is composed of a synthetic, protein-reactive monomer and a collagen backing. The active side is covered with a protein-reactive monomer: N-hydroxysuccinimide functionalized polyethylene glycol (NHS-PEG). NHS-PEG rapidly affixes the collagen pad to tissue to promote and maintain hemostasis. The combined action of the NHS-PEG and collagen is demonstrated to have benefit relative to other hemostatic agents in surgery and preclinical surgical models. This paper reviews the published investigations and case reports of the hemostatic efficacy of HEMOPATCH, wherein HEMOPATCH is demonstrated to be an effective, easy-to-use hemostatic agent in open and minimally invasive surgery of patients with thrombin- or platelet-induced coagulopathies. Keywords: HEMOPATCH, hemostasis, surgical hemostasis, sealing, surgical sealant